Contract governance and buyer–supplier conflict: The moderating role of institutions - Bai, Xuan; Sheng, Shibin; Li, Julie Juan (Journal of Operations Management, 2016)
AbstractDrawing on contract governance literature and institutional theory, this study investigates the differential effects of output‐ and behavior‐based contract governance on buyer–supplier conflict in supply chains. The authors develop a contingent perspective to examine how institutional factors moderate the impact of contract governance. The findings, from an empirical study of buyer–supplier dyads in China, show that an output‐based contract is negatively, whereas a behavior‐based contract is positively, related to buyer–supplier conflict. The effects of a contract are moderated by two primary institutional factors: legal enforceability and unilateral government support. These findings have important implications for supply chain research, public policy, and managerial practice.